Confinement and the Hatred of Sound in Times of COVID-19: A Molotov Cocktail for People With Misophonia - Ferrer-Torres, Antonia; Giménez-Llort, Lydia (Frontiers in Psychiatry, 2021)
Forced strict confinement to hamper the COVID-19 pandemic seriously affected people suffering from misophonia (M+) and those living with them. Misophonia is a complex neurophysiological and behavioral disorder of multifactorial origin, characterized by an intense physiological and emotional response produced by intolerance to auditory stimuli of the same pattern, regardless of physical properties. The present work studied the secondary impact that strict confinement caused in 342 adults (224 women:118 men) regularly attending a medical psychological center in Barcelona. Misophonia, usually underdiagnosed, showed a prevalence of 35%, the same for women (37%) than men (31%).A retrospective analysis using a physical-psychological-social inventory of 10 variables evaluated the number of individuals that during confinement and self-confinement (March 11 - June 29, 2020) canceled (mostly M-) and/or requested a therapeutic intervention, the reasons for their request, and the strategies they used to self-manage the situation. Ten main variables indicated that the confinement exponentially increased the effects of misophonia compared with results from the same individuals during the last quarter of 2019. Most people diagnosed with misophonia continued with tele-assistance during the confinement because of this impact's self-concern. Besides the impacts as part of the general population, M+ also developed different symptoms causing significant personal, social, and job/occupational imbalance, as compared to M-. Health, fears, conflicts with neighbors, study-related difficulties were outstanding reasons for consultations. The LSB-50 test for 'Psychological and Psychosomatic Symptoms' applied to M+ revealed the increase of 8 of 9 items of this psychopathological test. Sleep disorders (coronasomnia), hostility, depression, and somatization were more severe than in previous assessments. Women presented the worst psychological and psychosomatic states (8 out of 9, as compared to 1 out of 9 in males). The study unveiled the complex physical-psychological-social burden, the need for dissemination and a gender perspective to understand the secondary impact of COVID-19 pandemic on the mental health of the population with misophonia. The results also show that in this new COVID era people suffering from misophonia need to develop coping strategies addressing modifiable risk and protective factors. They deserve familial/social comprehension, stronger clinical support and a gender medicine perspective.